Gestão da cadeia de suprimento da lã em Santana do Livramento: uma análise a partir da COOFITEC - Lopes, Daniela Ferreira (2018)
The present study was carried out in the wool cooperative with the objective of analyzing the wool supply chain from COOFITEC in Santana do Livramento. The concepts of the supply chain were used in theory. The research is a case study, to be carried out a direct observation was made in the cooperative, analyzing the wool production process, access to the cooperative documents and interview with the president, identifying the members of the supply chain of the cooperative. Through the results, the key processes of the supply chain were identified. It was observed that it has a supply chain, but that is not defined by the cooperative, being far from the logistics, technology and information system. It is observed that the cooperative has a greater concern with its production, to the detriment of aspects of management and commercialization.